OCT-guided “Combo therapy” for a severely calcified bifurcation (LAD/D1): A case report - Suman Bhandari; Gajinder Pal Singh Kaler; Gary S. Mintz (IHJ Cardiovascular Case Reports, 2022)
OCT can assess the extent and depth of calcification in severely calcific coronary lesions to define the most apt lesion-modification therapy. We present a 56-year-old male with a severely calcific LAD/D1 bifurcation lesion requiring rotablation prior to OCT, followed by a 2 mm cutting balloon for lesion preparation. Subsequently a 2.25 × 32 mm stent was post-dilated to 24atm with an NC balloon. However, a waist necessitated subsequent post-dilation with a 2.5 × 10 mm OPN NC balloon at 38 atm. OCT vessel sizing and accurate plaque characterization allowed a successful outcome in this complex situation.